2014
DOI: 10.1890/13-2094.1
|View full text |Cite
|
Sign up to set email alerts
|

Community context mediates the top‐down vs. bottom‐up effects of grazers on rocky shores

Abstract: Abstract. Interactions between grazers and autotrophs are complex, including both topdown consumptive and bottom-up facilitative effects of grazers. Thus, in addition to consuming autotrophs, herbivores can also enhance autotroph biomass by recycling limiting nutrients, thereby increasing nutrient availability. Here, we evaluated these consumptive and facilitative interactions between snails (Littorina littorea) and seaweeds (Fucus vesiculosus and Ulva lactuca) on a rocky shore. We partitioned herbivores' tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Research in kelp forests (Bray et al, , ; Hepburn & Hurd, ) and temperate tidepools (Bracken, Dolecal, & Long, ; Bracken & Nielsen, ) has shown that consumers enhance nutrient cycling and primary production. Bray et al () found that benthic macroinvertebrates and fishes collectively supplied 25–30 µmol NH 4 + m −2 hr −1 in kelp forests off Catalina Island, CA, similar to rates supplied by macroinvertebrates in our study system.…”
Section: Discussionmentioning
confidence: 99%
“…Research in kelp forests (Bray et al, , ; Hepburn & Hurd, ) and temperate tidepools (Bracken, Dolecal, & Long, ; Bracken & Nielsen, ) has shown that consumers enhance nutrient cycling and primary production. Bray et al () found that benthic macroinvertebrates and fishes collectively supplied 25–30 µmol NH 4 + m −2 hr −1 in kelp forests off Catalina Island, CA, similar to rates supplied by macroinvertebrates in our study system.…”
Section: Discussionmentioning
confidence: 99%
“…In the Serengeti, for example, seasonal shortage of suitable food limits populations of large herbivores, while small herbivores are controlled primarily by carnivores (Sinclair et al 2010). Even in the rocky intertidal, an iconic example of top-down control of community structure and diversity (Paine 1966), the simultaneous importance of bottom-up processes is revealed by regional-scale comparisons among sites that differ in oceanographic parameters such as water column productivity and wave exposure (e.g., Menge 2000), as well as by mechanistic understanding of how context influences particular interactions (e.g., Bracken et al 2014). …”
mentioning
confidence: 99%
“…Plants may also directly benefit from throughfall nutrient inputs (especially when not having to compensate for severe herbivory‐induced biomass losses) as suggested for instance in a recent publication on potential facilitative effects among differently palatable seaweed species (Bracken et al ). We therefore analysed biomass log response ratios of plant communities finding that all communities responded negatively to herbivory, none fully compensating for biomass losses.…”
Section: Discussionmentioning
confidence: 99%